Differential Associations of Cystatin C Versus Creatinine‐Based Kidney Function With Risks of Cardiovascular Event and Mortality Among South Asian Individuals in the UK Biobank - Chen, Debbie C.; Lees, Jennifer S.; Lu, Kaiwei; Scherzer, Rebecca; Rutherford, Elaine; Mark, Patrick B.; Kanaya, Alka M.; Shlipak, Michael G.; Estrella, Michelle M. (Journal of the American Heart Association, 2023)
Background South Asian individuals have increased cardiovascular disease and mortality risks. Reliance on creatinine- rather than cystatin C-based estimated glomerular filtration rate (eGFRcys) may underestimate the cardiovascular disease risk associated with chronic kidney disease. Methods and Results Among 7738 South Asian UK BioBank participants without prevalent heart failure (HF) or atherosclerotic cardiovascular disease, we investigated associations of 4 eGFRcys and creatinine-based estimated glomerular filtration rate categories (<45, 45-59, 60-89, and ≥90 mL/min per 1.73 m ) with risks of all-cause mortality, incident HF, and incident atherosclerotic cardiovascular disease. The mean age was 53±8 years; 4085 (53%) were women. Compared with creatinine, cystatin C identified triple the number of participants with estimated glomerular filtration <45 (n=35 versus n=113) and 6 times the number with estimated glomerular filtration 45 to 59 (n=80 versus n=481). After multivariable adjustment, the eGFRcys 45 to 59 category was associated with higher risks of mortality (hazard ratio [HR], 2.38 [95% CI, 1.55-3.65]) and incident HF (sub-HR [sHR], 1.87 [95% CI, 1.09-3.22]) versus the eGFRcys ≥90 category; the creatinine-based estimated glomerular filtration rate 45 to 59 category had no significant associations with outcomes. Of the 7623 participants with creatinine-based estimated glomerular filtration rate ≥60, 498 (6.5%) were reclassified into eGFRcys <60 categories. Participants who were reclassified as having eGFRcys <45 had higher risks of mortality (HR, 4.88 [95% CI, 2.56-9.31]), incident HF (sHR, 4.96 [95% CI, 2.21-11.16]), and incident atherosclerotic cardiovascular disease (sHR, 2.29 [95% CI, 1.14-4.61]) versus those with eGFRcys ≥90; those reclassified as having eGFRcys 45 to 59 had double the mortality risk (HR, 2.25 [95% CI, 1.45-3.51]). Conclusions Among South Asian individuals, cystatin C identified a high-risk chronic kidney disease population that was not detected by creatinine and enhanced estimated glomerular filtration rate-based risk stratification for mortality, incident HF, and incident atherosclerotic cardiovascular disease.